EXPRESSÃO MILITAR DO SETOR ESTRATÉGICO ESPACIAL: EVOLUÇÃO E O DIREITO. CASO BRASILEIRO: QUARTA GERAÇÃO DA FORÇA AÉREA BRASILEIRA: José Vagner Vital, Maria Helena Fonseca de Souza Rolim (De Legibus - Law Journal, 2021)
The evolution and transformation of space technology interconnected with the military use of outer space highlights the pressure of the facts on the law, calling for reflection on the international corpus juris on the issue, at the level of soft law and hard law. Even in the context of self-defense, military space activities have offensive and defensive aspects that need to be considered and can be carried out under the United Nations Charter (considering the right to self-defense) and the Space Treaty (when understanding the term “peaceful purpose” equivalent to the term “non-aggression”, except for self-defense), in addition to other treaties that can be evoked in conflict situations, adopted by the International Humanitarian Law. This article sought to bring the Brazilian case, where the Brazilian Air Force translated Brazil’s understanding of the Space Treaty and the United Nations Charter, structuring its military application of outer space according to the political and doctrinal documents from the Brazilian Ministry of Defense, known as the National Defense Policy, the National Defense Strategy and the Strategic Space Systems Program. The military operations described in this article reveal that emerging factual situations lack legal protection with a high degree of effectiveness.